Annealing Effect on Improving the Mechanical Properties of Zirconium Based Biomaterials with the Addition of Yttrium Elements for Bone Plate Application - Awwaluddin, Muhammad; Prajitno, Djoko Hadi; Soemardi, Tresna P.; Hastuty, Sri (Piston: Journal of Technical Engineering, 2024)
To improve the mechanical properties of biomaterials with zirconium-based alloys, especially on ductility, an annealing process was carried out. The process was carried out at a temperature of 800 oC and holding time for 3 hours in a vacuum chamber which was flowed by high purity argon gas. The composition of the alloy used in this study was Zr6Mo4TixY (x= 0, 1 and 3 %wt). Microstructure observations were carried out using microscope optic and Scanning Electron Microscopy (SEM) and mechanical properties observation using tensile testing. In this study, micro-sized specimens were used and followed the ASTM E8-04 standard with a surface roughness of 1µm. The results showed an increase in the tensile strength value after annealing process and decrease the modulus elasticity. In addition, the grain boundaries of the alloy are getting smaller, this shows the effect of annealing on changes in the properties of the material.